Sunflower - Schwartz, David M.; Kuhn, Dwight (California : Creative Teaching Press, 1999)
Photographs and text trace the life cycle of sunflowers, from seed, to seedling, to stalk, to flower.
Includes bibliographical references (p. 23) and index.
4.1
K-3.
K-3
Keywords: Sunflowers -- Life cycles -- Juvenile literature; Sunflowers; Sunflowers